2010
DOI: 10.1097/phh.0b013e3181af63bb
|View full text |Cite
|
Sign up to set email alerts
|

Local Public Health Departments in California

Abstract: The purpose of this research was to assess California public health departments capacity, practices, and resources for changing nutrition and physical activity environments for obesity prevention. The researchers surveyed key public health department personnel representing all 61 health departments in California using a Web-based survey tool. The response rate for the survey was 62 percent. This represented a 93 percent health department response rate. Analysis was conducted on the individual respondent and pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Managers estimated 152 % more specialist nutrition and 131 % more specialist physical activity workforce was required to achieve policy/program goals. The findings are consistent with research in California which found 70 % of local public health department managers rated their staff capacity for obesity prevention in NAPA environments as less than effective [33]. …”
Section: Discussionsupporting
confidence: 88%
“…Managers estimated 152 % more specialist nutrition and 131 % more specialist physical activity workforce was required to achieve policy/program goals. The findings are consistent with research in California which found 70 % of local public health department managers rated their staff capacity for obesity prevention in NAPA environments as less than effective [33]. …”
Section: Discussionsupporting
confidence: 88%
“…5,6 This includes a spectrum of strategies such as making school menus healthier, establishing wellness policies in organizations, and increasing access to healthful foods and physical activity in communities. 5,6 While staff of public health and service agencies are familiar with working on the individual and interpersonal levels involving families, 7,8 they are being urged to mobilize their resources to promote changes on the organizational and community levels that can support healthy eating and physical activity to prevent obesity. 9–12 This study focused on actions to effect environmental changes, meaning changes that modify any contexts external to the individual, in organizations , e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, the application of the socio-ecological perspective to obesity prevention was not widespread until the early 2000’s 13 and this is still a new concept for many in public health 7 and community service work. For example, staff of the California public health system reported a lack of knowledge and skills to participate in environmental change work.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations